2015
DOI: 10.1016/j.drugalcdep.2015.07.501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an exercise intervention on methamphetamine use outcomes post residential treatment care

Abstract: Background-We examined the efficacy of an 8-week exercise intervention on posttreatment methamphetamine (MA) use among MA-dependent individuals following residential treatment.Methods-135 individuals newly enrolled in treatment were randomly assigned to a structured 8-week exercise intervention or health education control group. Approximately 1 week after completion of the intervention, participants were discharged to the community. Interview data and urine samples were collected at 1-, 3-, and 6-months post-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 32 publications
1
24
0
5
Order By: Relevance
“…The use of a median split to define an adequate exercise dose resulted in a dose that was at least two-thirds of the assigned dose. This rate is comparable to other studies of exercise in SUD [ 51 , 52 ]. Given the difficulties experienced by participants in STRIDE regarding adherence to the exercise program, future research is also needed to examine strategies to improve exercise adherence.…”
Section: Discussionsupporting
confidence: 89%
“…The use of a median split to define an adequate exercise dose resulted in a dose that was at least two-thirds of the assigned dose. This rate is comparable to other studies of exercise in SUD [ 51 , 52 ]. Given the difficulties experienced by participants in STRIDE regarding adherence to the exercise program, future research is also needed to examine strategies to improve exercise adherence.…”
Section: Discussionsupporting
confidence: 89%
“…Combined pharmacotherapies have been used clinically over the years for stimulant use disorders, and they have not been widely effective (see review, Stoops & Rush ). However, our recent data suggest that combination treatments involving a rewarding behavioral component (physical exercise) are effective in animals, and a recent study of methamphetamine abusers using physical exercise (Rawson et al ) reduced methamphetamine use in participants with more frequent use of exercise. Thus, an additional advantage of this treatment combination is that this approach may be self‐sustaining.…”
Section: Sex and Hormonal Differences In Treatment For Addictionmentioning
confidence: 88%
“…Accordingly, initial reports in human studies suggest that more exposure to environmental enrichment (e.g. exercise) increased its effectiveness (Rawson et al ).…”
Section: Sex and Hormonal Differences In Treatment For Addictionmentioning
confidence: 99%
“…The present findings show the durability of the SACC treatment as a sustainable, nondrug reward to achieve voluntary abstinence from illicit drug use on a long-term basis in humans. However, while SACC was used in our monkey laboratory to achieve reduced drug intake (see reviews by Carroll and Lynch 2016, Carroll and Smethells 2016), a healthy nondrug reward, such social/community reinforcement (Higgins et al 2003, 2008), physical exercise (Bardo and Compton 2015; Zhou et al 2015; Rawson et al 2015), or an employment-based therapeutic workplace (e.g., Silverman et al 2002) are suitable nondrug alternatives for application to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present study we compared cocaine intake during the luteal phase when serum PRO peaks in rhesus monkeys to the follicular phase when estrogen peaks (Cooper et al 2013), and we compared cocaine intake during the luteal and follicular phases. Recently it was shown that physical exercise reduced methamphetamine use in humans undergoing a residential treatment program (Rawson et al 2015). Others have shown that nondrug alternative rewards reduce drug-seeking in animals (Foltin et al 2015) and humans (Foltin et al 2015; Higgins et al 2008).…”
Section: Introductionmentioning
confidence: 99%